(untitled) (Global Journal of Management and Business Research, 2020)
This paper tries to explore the culture effect on strategic planning practices in Kenya, specifically focusing on a survey of public secondary schools in Migori County. The study employed descriptive research design. The target population constituted public secondary schools in Migori county drawing respondents from school principals, their deputies, and heads of departments whose total was 1056. Stratified random sampling was used to draw a sample size of 106 respondents. The study used a Questionnaire for primary data collection and administered it using a drop and pick method, which helped minimize financial and time limitations that the researcher was likely to face. Quantitative data was collected and analyzed using descriptive statistics. The results of the study indicated that there was an outstanding relationship between organizational culture and strategic management practices.